Self-reported pedestrian behaviour in Australia. (November 2020) - O'Hern, Steve; Stephens, Amanda N.; Estgfaeller, Nora; Moore, Victoria; Koppel, Sjaan
Highlights: We validated a pedestrian behaviour questionnaire for Australia. The most frequent behaviours involved using technology while walking. The most infrequent behaviours were unintentional errors. Males reported higher engagement in all behaviours. Age was negatively associated with errors, violations and use of technology. Abstract: Internationally, there have been a number of self-reported questionnaires developed to classify pedestrians' engagement in aberrant behaviours while walking. However, there is yet to be consensus regarding the most appropriate factor structure for these models. Furthermore, to our knowledge, a pedestrian behaviour questionnaire (PBQ) has not been validated to investigate Australian pedestrians. As such, the aim of this research was to build on the previous international instances of pedestrian behaviour questionnaires and validate a questionnaire for a cohort of Australians. Nine hundred and sixty eight participants (80.8% female) completed an online survey which included 128 items describing pedestrian behaviour, identified in international versions of PBQs. A split half analysis was conducted to determine the most appropriate configuration of the scale. Exploratory Factor Analysis conducted on half of the sample identified a 32-item four factor model of pedestrian behaviour. These factors broadly described unintentional errors, deliberate violations, aggression and engagement with technology. Confirmatory Factor Analysis on the remaining sample confirmed the proposed factor structure. Across the four factors, pedestrians reported low mean scores for all items; indicating that errors, violations, technology engagement and aggression were rarely exhibited behaviours. The highest mean scores were for engagement with technology. While the least common pedestrian behaviours were errors while walking. Male participants were found to self-report higher rates of all behaviours, while age was negatively associated with violations, errors and technology engagement. Overall, the research presents a validated measure of aberrant pedestrian behaviour in Australia.